Hybrid Electrodes of Carbon Nanotube and Reduced Graphene Oxide for Energy Storage Applications - Choi, Eunmi; Chae, Su Jin; Kim, Areum; Kang, Keun Won; Oh, Min Seok; Kwon, Soon Hyeong; Yoon, Sung Pil; Pyo, Sung Gyu (AMER SCIENTIFIC PUBLISHERS, 2015)
The choice of electrode materials in lithium ion batteries and supercapacitors is important for the stability, capacity, and cycle life of the device. Despite its low capacity, graphite has often been used as an electrode material due to its inherent stability. Due to an increasing demand for large-capacity energy storage systems, there is also a demand for the development of large-capacity Li ion batteries and supercapacitors. Therefore, carbonaceous materials like graphene and carbon nanotubes (CNTs), which have high stability as well as excellent electrical conductivity and mechanical strength, are receiving attention as new electrode materials. Recently, starting from simply applying graphene and CNTs as electrode materials and progressing to the development of hybrid materials, there have been increasing research efforts in enhancing the performance of Li ion batteries and supercapacitors through the use of carbonaceous materials. This paper will discuss new composite materials and electrode structures that use graphene and CNTs for applications in Li ion batteries and supercapacitors.
Keywords: LITHIUM-ION BATTERY; HIGH-RATE CAPABILITY; HIGH-PERFORMANCE; CONDUCTING-POLYMER; ELECTROCHEMICAL PROPERTIES; COMPOSITE ELECTRODES; LIFEPO4 CATHODE; METAL-OXIDES; SUPERCAPACITOR; ANODE